The Effect of Lemongrass, Ginger, Turmeric, and Javanese Ginger Mixture on Reducing Dysmenorrhea Pain - Oktavia, Nadiva; Wahyuningrum, Ari Damayanti; Ekasari, Rizqiana Dita (Jurnal Maternitas Kebidanan, 2025)
Dysmenorrhea is caused by hormonal imbalances that trigger lower abdominal pain, which may radiate to the suprapubic region, lower back, medial thighs, and perineum. Dysmenorrhea typically occurs 1–2 days before or during menstruation, causing disruptions in concentration and increased anxiety. Non-pharmacological management of dysmenorrhea with SJKT (Lemongrass, Ginger, Turmeric, Curcuma Xanthorrhiza) formulations, containing gingerol, shogaol, essential oils, flavonoids, polyphenols, and curcumin exerts analgesic effects that are effective in reducing pain. To analyze the effectiveness of SJKT formulations in reducing menstrual pain associated with dysmenorrhea. A true experimental design with a two-group pretest-posttest control group design was employed. The intervention group received SJKT formulations, while the control group consumed young coconut water, 300 ml/day for 4 days. The Wilcoxon test for the intervention group yielded a p-value of 0.001, while the control group had a p-value of 0.157. The Mann-Whitney test produced a p-value of 0.022, showing a significant difference between the two groups, as the SJKT formulation is more effective in reducing dysmenorrhea pain compared to young coconut water. SJKT formulation effectively reduces dysmenorrhea pain. Further studies could involve larger samples for more comprehensive results.